2008
DOI: 10.1590/s0101-20612008000400009
|View full text |Cite
|
Sign up to set email alerts
|

Valor nutricional e características químicas e físicas de frutos de murici-passa (Byrsonima verbascifolia)

Abstract: IntroduçãoO murici (Byrsonima ssp., Malpighiaceae) é um fruto do Cerrado consumido principalmente in natura, sendo encontrado de dezembro a março, nas regiões serranas do Sudeste, nos cerrados de Mato Grosso e Goiás e no litoral do Norte e Nordeste do Brasil. Quando maduro, apresenta-se amarelado, com diâmetro de 1,5 a 2 cm e um forte odor semelhante a queijo rançoso (REZENDE;FRAGA, 2003;ALVES;FRANCO, 2003). Sua comercialização se restringe às feiras livres e mercados locais. A polpa é carnosa e macia, podendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
6
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 1 publication
3
5
6
11
Order By: Relevance
“…The soluble solids concentration found in the murici pulp of fruit from Minas Gerais, Brazil (10.73°Brix) (table II) was similar to that reported by Guimarães and Silva [21] (10.67°Brix) in fruits collected in the state of Goiás, and higher than that found by Canuto et al [22] in fruits from the Amazon (1.5°Brix). The higher soluble solids content found in our study compared with that reported in previous studies may be explained by the difference in the states (which have different climates) in which the …”
Section: Physicochemical Characterizationsupporting
confidence: 87%
See 1 more Smart Citation
“…The soluble solids concentration found in the murici pulp of fruit from Minas Gerais, Brazil (10.73°Brix) (table II) was similar to that reported by Guimarães and Silva [21] (10.67°Brix) in fruits collected in the state of Goiás, and higher than that found by Canuto et al [22] in fruits from the Amazon (1.5°Brix). The higher soluble solids content found in our study compared with that reported in previous studies may be explained by the difference in the states (which have different climates) in which the …”
Section: Physicochemical Characterizationsupporting
confidence: 87%
“…The murici pulp in the fruits we collected in Minas Gerais presented a pH greater than the 3.42 reported by Guimarães and Silva [21] in fruits collected in Goiás, and pH 3.7 observed by Canuto et al [24] in fruits of the Amazon.…”
Section: Fr Hamacek Et Alcontrasting
confidence: 62%
“…Possui hábito subarbustivo (Barbosa et al, 2005) e folhas grandes e rígidas (Andrade et al, 1995), com pêlos em ambas faces (Andrade et al, 1995;Andrade et al, 1999). O fruto dessa espécie possui coloração amarela (Guimarães & Silva, 2008;Alberto et al, 2011), diâmetro entre 1,50 à 2 cm com cheiro forte semelhante a queijo rançoso (Guimarães & Silva, 2008), sabor azedo e ligeiramente oleoso (Araújo et al, 2009). A madeira possui coloração amarelada ou avermelhada e brilhante (Alberto et al, 2011).…”
Section: Descrição Botânicaunclassified
“…A. Juss é uma espécie típica do cerrado brasileiro com elevada densidade no Centro-Oeste e Norte do Brasil (Barbosa & Fearnside, 2004;Barbosa et al, 2005) e com baixa biomassa (Barbosa & Fearnside, 2004). A produção de frutos nesta espécie ocorre de dezembro a março, nas regiões serranas do Sudeste nos cerrados do Mato Grosso e Goiás e litoral do Norte e Nordeste do Brasil (Guimarães & Silva, 2008).…”
Section: Distribuição E Ocorrênciaunclassified
See 1 more Smart Citation